PENGARUH PEMBERIAN REBUSAN DAUN SIRIH TERHADAP PENYEMBUHAN LUKA PERINIUM PADA IBU NIFAS DI KLINIK PRATAMA SEHATI HUSADA KECAMATAN SIBIRU-BIRU TAHUN 2026 - Stefani Anastasia Sitepu (JURNAL ILMIAH DHDT - KEBIDANAN, 2026)
Injuries to the birth canal that occur during childbirth, whether instrumental or non-instrumental, are known as perineal ruptures. Causes of perineal rupture include parity, fetal weight, improper labor position, rigid perineum, forceps extraction, vacuum extraction, instrument trauma, and episiotomy. To prevent infection of the perineal wound due to tears or episiotomy, vulvar hygiene is crucial. Postpartum wound care to prevent infection is strongly influenced by several factors, including communication, information, and education (IEC) provided by health workers. Based on the results of the research, it can be concluded that there is a significant effect of lavender aromatherapy and back massage on the sleep quality of pregnant women in the third trimester at the Sehati Husada Primary Clinic, Sibiru-biru District in 2026. The results of the T-test obtained a p-value of 0.000 (P <0.05), which means there is a significant effect. These results indicate that natural-based interventions, such as betel leaf, have high potential as part of independent nursing practice during the postpartum period. By significantly reducing REEDA scores, these interventions can accelerate maternal physical recovery, reduce perineal discomfort and pain, improve maternal quality of life and mobility during the postpartum period, and prevent the risk of infection and wound complications.